Optimization of in-brace corrective force in adolescents with Lenke type 5 curve using finite element model. - Li, Kepeng; Wu, Jincheng; Yang, Dongmei; Xu, Hanpeng; Wen, Wangqiang; Xu, Haoxiang; Ma, Guoju; Han, Ye (Journal of Orthopaedic Surgery & Research, 2023)
Background: Pelvic parameters have been taken into consideration for the evaluation of the outcomes of bracing in AIS. To discuss the stress required to correct the pelvic deformity related to Lenke5 adolescent idiopathic scoliosis (AIS) by finite element analysis, and provide a reference for the shaping of the pelvic region of the brace. Methods: An three-dimensional (3D) corrective force on the pelvic area was defined. Computed tomography images were used to reconstruct a 3D model of Lenke5 AIS. Computer-aided engineering software Abaqus was used to implement finite element analysis. By adjusting the magnitude and position of corrective forces, coronal pelvic coronal plane rotation (PCPR) and Cobb angle (CA) of lumbar curve in the coronal plane, horizontal pelvic axial plane rotation, and apical vertebra rotation (AVR) were minimized to achieve the best effect on the spine and pelvic deformity correction. The proposed corrective conditions were divided into three groups: (1) forces applied on X-axis; (2) forces applied both in the X- and Y-axis; and (3) forces applied along the X-, Y-, and Z-axis at the same time. Results: In three groups, CA correction reduced by 31.5%, 42.5%, and 59.8%, and the PCPR changed to 12°, 13°, and 1° from 6.5°, respectively. The best groups of correction forces should simultaneously locate on the sagittal, transverse, and coronal planes of the pelvis. Conclusions: For Lenke5 AIS, 3D correction forces can sufficiently reduce scoliosis and pelvic asymmetrical state. Force applied along the Z-axis is vital to correct the pelvic coronal pelvic tilt associated with Lenke5 AIS.